Henry and Mudge and the Great Grandpas - Rylant, Cynthia; Stevenson, Sucie (New York, 2005)
When Henry and his dog Mudge go with Henry's parents to visit Great-Grandpa Bill in the home with lots of other grandpas, they lead them all on a wonderful adventure.
Ages 5-7.